Physicians Perceptions of Shared Decision-Making in Neonatal and Pediatric Critical Care. (April 2018) - Richards, Claire A.; Starks, Helene; O'Connor, M. Rebecca; Bourget, Erica; Hays, Ross M.; Doorenbos, Ardith Z.
Background: Most children die in neonatal and pediatric intensive care units after decisions are made to withhold or withdraw life-sustaining treatments. These decisions can be challenging when there are different views about the child's best interest and when there is a lack of clarity about how best to also consider the interests of the family. Objective: To understand how neonatal and pediatric critical care physicians balance and integrate the interests of the child and family in decisions about life-sustaining treatments. Methods: Semistructured interviews were conducted with 22 physicians from neonatal, pediatric, and cardiothoracic intensive care units in a single quaternary care pediatric hospital. Transcribed interviews were analyzed using content and thematic analysis. Results: We identified 3 main themes: (1) beliefs about child and family interests; (2) disagreement about the child's best interest; and (3) decision-making strategies, including limiting options, being directive, staying neutral, and allowing parents to come to their own conclusions. Physicians described challenges to implementing shared decision-making including unequal power and authority, clinical uncertainty, and complexity of balancing child and family interests. They acknowledged determining the level of engagement in shared decision-making with parents (vs routine engagement) based on their perceptions of the best interests of the child and parent. Conclusions: Due to power imbalances, families' values and preferences may not be integrated in decisions or families may be excluded from discussions about goals of care. We suggest that a systematic approach to identify parental preferences and needs for decisional roles and information may reduce variability in parental involvement.